Tinjauan Sanitasi Usaha Salon Kecantikan Di Painan Kabupaten Pesisir Selatan - Putri Ayu; Linda Rosalina (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2020)
Abstract The problem in this research is still a lack of awareness of beauty salon business owners in registering business units in related institutions (Office of Integrated Licensing Service). Still the low supervision of the business sanitation beauty salon seen from various aspects a) the feasibility of building, B) The quality of clean water, c) waste management, c) sewage control and D) hygiene tools and cosmetic materials. This research aims to describe the business sanitation of the beauty salon in the South Coastal district of Painan. This type of research is quantitative descriptive. The population of this research is the head and employee of the beauty salon in the south coast of 17 people. Data retrieval techniques are using questionnaires that are adjusted in the form of Likert scales that have been tested for validity and reliability. Data analysis techniques using percentage and categorizing formulas. Based on the known research results of beauty salon sanitation based on building feasibility of good category with an average value of 14.05, clean water feasibility is good with an average value of 20.11, waste management is good with An average value of 26.05, good waste control with an average value of 18.41 and sanitary beauty salons based on the cleanliness of the cosmetic tool well with an average value of 39.70. It is expected for salon owners and employees to pay more attention to and improve the sanitation of beauty Salona business in Painan South Coast district in all aspects, it is expected to create a clean, comfortable and safe environment from Various diseases arising from the business environment. Keywords: Sanitation, Business Beauty Salon